Analisis Riset Harga Terhadap Keputusan Pembelian Es Krim Aice Pada Mahasiswa Universitas Bina Bangsa - Aryati Aryati; Ayu Nuryani; Syamsul Hidayat (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this study was to analyze the effect of price research on purchasing decisions for ice cream products.This research uses quantitative methods and takes a sample of 150 Bina Bangsa University students who consume Aice ice cream. Data was collected by distributing questionnaires and processed using SPSS software analysis tools. Test selected results and quantitative analysis include validity test, reliability test, simple linear aggressiveness test, t test, f test, and coefficient of determination test.Based on the research results, it is concluded that the price variable has a positive and significant effect on consumer purchasing decisions for ice cream.